"Nobody Sees It, Nobody Gets Mad": Social Media, Privacy, and Personal Responsibility Among Low-SES Youth. (May 2017) - Marwick, Alice; Fontaine, Claire; boyd, danah
While few studies examine the online privacy practices or attitudes of young people of low socio-economic status (SES), they are often at the most risk of and most susceptible to privacy violations. This participatory, collaborative study of 28 low-SES young adults in the New York City area investigates how they view online information sharing. Like most Americans, our participants viewed online privacy as an individual responsibility. We make two primary contributions. First, participants revealed extensive awareness of the risks of sharing information online, and many avoided social media, self-censored, or obfuscated their contributions as a result. Second, many participants had extensive experience with policing and physical surveillance and were aware they could not avoid such encounters through their own efforts. This window into structural discrimination provides an alternate frame to that of "individual responsibility" that educators and researchers can use to conceptualize how privacy is violated online. Framing online privacy violations as inevitable and widespread may not only help foster activist anger and strategic resistance but also avoid the victim-blaming narratives of some media literacy efforts. By examining the experiences of these young people, who are often left out of mainstream discussions about privacy, we hope to show how approaches to managing the interplay of on- and offline information flows are related to marginalized social and economic positions.